STUDY OF SOURCE ROCK IDENTITY ON LAGAN AND RAMBUTAN AREA USING GEOCHEMICAL INVERSION METHOD, SOUTH SUMATRA BASIN - PAMADYA ( NIM : 12010071 ), YOGI
Lagan and Rambutan are part of PT Medco E&P working area in South Sumatra Basin. This research aims to study about geological condition and to determine the source rock of the research area based on geochemical characteristics of the oil (geochemical inversion method). The stratigraphic of Lagan and Rambutan consists of basement rock, Lemat Formation, Talangakar Formation, Telisa (Gumai) Formation, and Airbenakat Formation. Geological structure of research area is half graben system that is compiled by north-south normal faults. In addition, there are highland and depression structure around research area. Analyses of biomarker geochemistry on oil samples are used to find out the geochemical characteristics of oil samples. The geochemical characteristics of oil will be used to determine the possible identity of source rock in this research area. Analyses of biomarker on oil samples shows the organic materials derived from alga/bacteria, mixed materials, and higher plants with anoxic to oxic condition. The oil samples are deposited on transition zone.The source rocks that have sufficient organic material richness and maturity to produce hydrocarbon in the research area are Lemat Formation and Talangakar Formation. Based on biomarker analyses, Lemat Formation and Talangakar Formation have similar geochemical characteristics and depositional system with the oil samples. Biomarker correlation analyses show that some oil samples are trendly correlated in geochemical characteristics with some Talangakar Formation samples. The oil is assumed migrating laterally from Talangakar Formation or Lemat Formation to the research area and vertically through long faults beneath the research area.